Deflection of Coronal Mass Ejections in Unipolar Ambient Magnetic Fields - Michal Ben-Nun; Tibor Török; Erika Palmerio; Cooper Downs; Viacheslav S. Titov; Mark G. Linton; Ronald M. Caplan; Roberto Lionello (The Astrophysical Journal, 2023)
The trajectories of coronal mass ejections (CMEs) are often seen to deviate substantially from a purely radial propagation direction. Such deviations occur predominantly in the corona and have been attributed to “channeling” or deflection of the eruptive flux by asymmetric ambient magnetic fields. Here, we investigate an additional mechanism that does not require any asymmetry of the preeruptive ambient field. Using magnetohydrodynamic numerical simulations, we show that the trajectories of CMEs through the solar corona can significantly deviate from the radial direction when propagation takes place in a unipolar radial field. We demonstrate that the deviation is most prominent below ∼15 R _⊙ and can be attributed to an “effective I × B force” that arises from the intrusion of a magnetic flux rope with a net axial electric current into a unipolar background field. These results are important for predictions of CME trajectories in the context of space-weather forecasts, as well as for reaching a deeper understanding of the fundamental physics underlying CME interactions with the ambient fields in the extended solar corona.